A High Efficiency Interleaved PFC Front – End Converter for EV Battery Charger - Giuseppe Aiello; Mario Cacciato; Sebastiano Messina; Marco Torrisi (Communications - Scientific letters of the University of Zilina, 2018)
Nowadays, an increasingly present application in the automotive field is the battery charger that usually consists of two high efficiency parts: an AC/DC converter with power factor correction (PFC) capability and a DC/DC converter. In this paper, a three-channel interleaved Power Factor Correction (PFC) based on a new digital controller STNRGPF01 operating in Continuous Conduction Mode (CCM) is presented addressing high efficiency. In the considered applications, the most challenging control issues are the input current control and the fast overcurrent protections. Exploiting mixed signal control approach some benefits have been obtained and confirmed by experimental results on a 3 kW prototype.